Diabetic foot: What to do and not to do - Mario Pappagallo (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2018)
Those who live with diabetes must pay attention to its extremities, especially the feet. It's just when you're feeling good, because you control your complicated relationship with sugars, here's a small abrasion, a badly cut nail, a callus, a bladder caused by fashionable shoes but not quite adapted to your foot, a mushroom can turn a banality into drama. Before designing a specifi c diabetic prevention plan - aimed at reducing the risk of neuropathic foot complications - it is necessary to identify the patient's risk factors and incorrect lifestyle habits.